Impact of nonlinearities on fiber optic communications - Kumar, Shiva Dr (Optical and fiber communications reports, 2011)
This book covers the recent progress in fiber-optic communication systems with a main focus on the impact of fiber nonlinearities on system performance. There has been significant progress in coherent communication systems in the past few years due to the advances in digital signal processing techniques. This has led to renewed interest in fiber linear and nonlinear impairments as well as techniques to mitigate them in the electrical domain. In this book, the reader will find all the important topics of fiber optic communication systems in one place, with in-depth coverage by the experts of each sub-topic. Pioneers from each of the sub-topics have been invited to contribute. Each chapter will have a section on fundamentals as well as reviews of literature and of recent developments. Readers will benefit from this approach since many of the conference proceedings and journal articles mainly focus on the authors' research, without spending space on preliminaries.